IMPLEMENTASI JARINGAN KOMPUTER PADA PERPUSTAKAAN BANK INDONESIA (BI) KEDIRI - Lutfi Fitriani (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
Bank Indonesia (BI) Library Kediri in implementing computer networks is quite adequate. Based on research in the field, the Bank Indonesia Kediri Library has not maximized computer network facilities for users or users. This is due to the constraints of the procurement process and the development of library space which results in constraints on various library facilities. This study aims to analyze the application or implementation of computer networks at the Bank Indonesia (BI) Kediri Library. The study was conducted through a qualitative descriptive research method with a type of case study on the application of computer networks in the Kediri BI library. Network devices that are implemented at KPw Bank Indonesia Kediri are MAN (Metropolitan Area Network). The network that is implemented in the Bank Indonesia Kediri library is a LAN (Local Area Network), which is connected to the network center in the BI office itself. The application of library automation is adequate with processing activities, availability of OPAC, circulation services and library reports. Various constraints on the network in the BI Kediri library inhibit the service process in the library, so there is a need for manual services so that services in the library such as the loan and return process continue to run.